PERUMAHAN DAN PERMUKIMAN TRADISIONAL BALI - Acwin Dwijendra, Ngakan Ketut (Jurnal Natah; Vol. 1, No. 1 Februari 2003)
Balinese Traditional Housing and Settlement is a place of unity and harmonious life that has a traditionally pattern and consists of three elements i.e. element of the village temple (kahyangan tiga), element of the village inhabitants (krama desa), and element of the village region (karang desa) and predominantly based on traditionally norm and value background. The Balinese Traditional Housing and Settlement is in essence sustained by concepts such as: harmonious relations between Bhuana Agung with Bhuana Alit, Manik Ring Cucupu, Tri Hita Karana, Tri Angga, Hulu-Teben till developing the value arrangement of Sanga Mandala that offers the guidance to the spatial pattern both on the house and the settlement scale. In this study, those concepts are mainly concluded into four aspects in the Balinese Traditional Housing and Settlement such as: a social, symbolic, morphology and functional aspects.
Keywords: Balinese Traditional Housing and Settlement, Concept, Pattern.